Pengaruh Terapi Spritual Emotional Freedom Technique terhadap Kualitas Tidur pada Lansia - Ichlas Tribakti; Syamsul Anwar; Nurhayati Nurhayati (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of SEFT therapy on sleep quality in the elderly. This research is quantitative research using a quasi experiment approach with a research design using a quasi experimental pretest-posttest with control group design. Sampling used purposive sampling technique with a total of 15 respondents each for the control group and 15 people for the intervention group. Pre and post sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results of the research, bivariate analysis with paired t test in the intervention group showed that there was a difference between sleep quality before and after the SEFT intervention with a P-Value of 0.012. Meanwhile, in the control group there was no difference between sleep quality before and after with a P-Value of 0.089. The results of statistical tests using the independent t test showed a significant difference between sleep quality in the intervention and control groups, p value = 0.004 < α (0.05). In conclusion, there is an influence of SEFT therapy on sleep quality in the elderly in Subangjaya Village. Suggestions for future researchers are using quantitative methods (Quasi Experimental) in mixed methods with qualitative which is expected to provide in-depth information about SEFT therapy. Keywords: Sleep Quality, Elderly, SEFT